1245. Outpatient Hepatitis C Management in Patients with Substance Use Disorder Following Hospital Admission for Severe Bacterial Infection. (15th December 2022) - Conte, Michael; Streifel, Amber C; Sikka, Monica K; Varley, Cara D
Abstract: Background: Patients with substance used disorder (SUD) are at high risk of hepatitis c virus (HCV) infection. During admission for acute illness, patients with SUD are often screened for or known to have untreated chronic HCV with outpatient follow-up recommended. However, many barriers to HCV treatment exists including lack of insurance, no primary care provider (PCP), drug cost, and transportation. Therefore, we aimed to investigate HCV follow-up and treatment in patients with SUD post-hospitalization. Methods: We performed a retrospective review of patients with SUD admitted for a severe bacterial infection between July 2015 and March 2020. A descriptive analysis was performed to evaluate patients with positive HCV testing instructed to follow-up outpatient for HCV treatment per discharge summary. We collected key information via chart review including location and attendance of follow-up as well as HCV testing and treatment status within two years of discharge. Results: We identified 108 patients during the study period with chronic HCV in which 48 were recommended follow-up for outpatient HCV treatment (Table 1). 38 (79.2%) were recommended to follow-up with PCP and 10 (20.8%) with hepatology. 15 patients (31.2%) made their follow-up appointment. 30 patients (62.5%) had documented repeat HCV testing within two years of discharge. Of these, one (3.3%) was HCV antibody (Ab) only, 10 (33.3%) were HCV Ab plus viral load (VL), and 19 (63.3%) were HCV VL alone. 41 patients (85.4%) had no evidence of HCV treatment and 7 (14.6%) had documented clearance (4 confirmed treatment, 2 presumed treatment, and one documented treatment without confirmed testing). Of the 7 treated, 4 (57.1%) had a PCP prior to admission, whereas in the 41 untreated, 5 (12.2%) had a PCP. Table 1: HCV Follow-Up Outcomes Conclusion: A low proportion of patients were confirmed to initiate and complete outpatient HCV therapy following hospital discharge. Many patients were lost to follow-up and had no repeat testing available. One-third of patients with repeat testing had repeat HCV Ab screen indicating an area for diagnostic stewardship. More pro-active approaches coordinating HCV therapy in patients with SUD requiring hospitalization for other infections are warranted in order to prevent unnecessary sequelae including HCV cirrhosis and carcinoma. Disclosures: Monica K. Sikka, MD, F2G: Site research investigator.